Advances in psychometric tests for screening minimal hepatic encephalopathy: From paper-and-pencil to computer-aided assessment - Luo, Ming; Ma, Ping; Li, Lei; Cao, Wu-Kui (Turkish Journal of Gastroenterology, 2019)
Abstract Minimal hepatic encephalopathy (MHE) is a major neuropsychiatric complication of liver cirrhosis and portosystemic shunting. Although MHE produces a spectrum of cognitive impairments in the domains of short-term attention, working memory, and executive function, it generally does not present with obvious clinical manifestation on conventional assessments. Paper-and-pencil psychometric tests, such as the psychometric hepatic encephalopathy score and the repeatable battery for the assessment of neuropsychological status, are recommended to diagnose MHE. However, these tests are neither rapid nor convenient to use in practice. To facilitate repeated testing in clinic and follow-up, computer-aided psychometric tests, such as the scan test, Cognitive Drug Research assessment battery, inhibitory control test, EncephalApp Stroop App, and critical flicker frequency, have been used to screen for MHE among patients with liver cirrhosis. The aim of this review was to describe the progression from the utility of paper-and-pencil to computer-aided psychometric tests for MHE screening in clinical practice. Cite this article as: Luo M, Ma P, Li L, Cao WK. Advances in psychometric tests for screening minimal hepatic encephalopathy: From paper-and-pencil to computer-aided assessment. Turk J Gastroenterol 2019; 30(5): 398-407.